Digital Satire as Political Discourse: Humor, Memes, and Resistance in Philippine Internet Culture - Ahmad Salman Farid; Anwar M Radiamoda (MD Research Center, 2026)
This study examines the emergence of humor and satire as a new form of political language within the digital culture of the Philippines. It aims to understand how political memes, parody videos, and satirical content function as instruments of political articulation in a society shaped by Catholic values, colonial legacies, and strong oral traditions. Employing a qualitative literature-based analysis, this research synthesizes findings from academic journals, scholarly books, and digital documents to explore the socio-political roles of digital humor. The findings reveal that digital humor serves not merely as entertainment but as a cultural strategy for negotiating power, fostering political solidarity, and expressing collective identity. It enables citizens to criticize authority and address social issues indirectly, aligning with Filipino communication norms of pakikisama (social harmony) and hiya (shame/honor). The study argues that digital humor is fundamentally ambivalent, it can act as a tool of resistance and emancipation while also reinforcing political propaganda and disinformation. This duality underscores the need for interdisciplinary approaches to better understand the complex interplay between digital culture, political participation, and socio-cultural characteristics in postcolonial contexts like the Philippines.